“A WOMAN IS A CHESTNUT, A MAN IS A BREADFRUIT”: PROVERBS AND FEMALE RESILIENCE IN SIMONE SCHWARZ-BART’S THE BRIDGE OF BEYOND - Mimko Bestman, Ajoke (Proverbium - Yearbook, 2017)
The Bridge of Beyond (1982, French original 1972) by Guadeloupian female writer, Simone Schwarz-Bart, depicts Caribbean women at the intersection of gender, race and class. Drawing inspiration from Caribbean oral tradition, itself a legacy of the African patrimony, the author makes copious use of proverbs in the novel. This study analyses some of the proverbs used by female characters from the womanist perspective. It focuses on the internalisation of the messages they encode and how these messages translate into effective means of resistance to various forms of adversity in the hostile post-emancipation Caribbean society. The study reveals that women in the novel and in tandem with the sociology of the Caribbean islands are the stabilising force of the family within a social structure that emasculates black men. The paper concludes that the tenacity and resilience of the women emanate from a positive world view gleaned from proverbs as a result of which they emerge as solid anchors of their families and, by extension, agents of the survival of their entire race.